Rachel Moran: Journey of a Prostitution Survivor to a Women's Liberation Leader. Issue 1 (June 2016) - Kakoty, Juanita
Rachel Moran is the author of Paid For and one of the key individuals who pushed for the Nordic Model in Ireland, whereby it became illegal to purchase sex in the country. As a survivor who has been courageous to tell her story and highlight the abuse and exploitation inherent in prostitution, she is an important voice in today's times. In conversation with Juanita Kakoty, she reflects on her current role as a key activist in the women's movement and her journey so far after she extricated herself from prostitution.